Communicating value to enhance service visualization - Leong, Vai Shiem; Hibbert, Sally; Ennew, Christine (Emerald, 2018)
Purpose – This study aims to examine the effects of enhanced visualization of intangible service value through integration of means-end perspectives on advertising effectiveness.